OPTIMASI PERENCANAAN SISTEM PEMBUMIAN PADA RENCANA PEMBANGUNAN GAS INSULATED SUBSTATION 150 KV PECATU - Putu Quentin MP; Cok Gede Indra Partha; IGN Janardana (Program Studi Teknik Elektro UNUD, 2020)
The construction of the Gas Insulated Substation (GIS) 150 kV Pecatu is planned by PT. PLN(Persero) to get electricity needs in the area of Pecatu, Badung Regency, Bali Province. The GasInsulated Substation (GIS) 150 kV Pecatu is located in a hilly area with a texture of limestone rockysoil and the resulting soil type resistance is ? = 263.76 ohm-meter. The results of calculations for thetype of earthing system Plates earth resistance value of 0.95 ohms at a cost of Rp. 4,196,000,000, -(Four Billion One Hundred Ninety Six Million Rupiah), for the type of Mesh earthing system no resultsare obtained <1 ohm and for the Multi Grid-Rod earthing system type the grounding resistance valueis 0.876 ohms at a cost of Rp 3,753,120,000, - (Three Billion Seven Hundred Fifty Three Million OneHundred Twenty Thousand Rupiah). The type of earthing system recommended is a Multi Grid-Rodearthing system with a distance between parallel conductors (D) of 1 meter, depth of conductorplanting as deep as 4 meters above the ground surface, Rod electrode diameter of 0.015 meters, Rodelectrode length of 4 meters and total conductor length of 12500 meters.